Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1002/(sici)1097-0142(19980715)83:2<254::aid-cncr8>3.3.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Protracted treatment with tegafur and low dose oral leucovorin in patients with advanced colorectal carcinoma

Miquel Nogué,
Miquel A. Seguí,
Eugeni Saigí
et al.

Abstract: The results of this study show that an all-oral regimen of tegafur and leucovorin can obtain biochemical modulation, with a significant response rate, in patients with advanced colorectal carcinoma. Randomized trials are needed to assess the possible advantage of this regimen over intravenous schedules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This combination attempts to simulate the continuous infusion of 5-FU and LV, with the advantage of an ambulant oral treatment. This scheme demonstrated a response rate comparable to that of the continuous infusion of 5-FU in advanced colorectal cancer (38.5%, 95% confi dence interval, 23.2-53.6%) [9], with an acceptable degree of toxicity. Afterwards, we performed a phase III study in metastatic colorectal cancer with a combination of FT and LV, showing that it has an activity equivalent to that of the Mayo schedule [10].…”
Section: Introductionmentioning
confidence: 78%
“…This combination attempts to simulate the continuous infusion of 5-FU and LV, with the advantage of an ambulant oral treatment. This scheme demonstrated a response rate comparable to that of the continuous infusion of 5-FU in advanced colorectal cancer (38.5%, 95% confi dence interval, 23.2-53.6%) [9], with an acceptable degree of toxicity. Afterwards, we performed a phase III study in metastatic colorectal cancer with a combination of FT and LV, showing that it has an activity equivalent to that of the Mayo schedule [10].…”
Section: Introductionmentioning
confidence: 78%
“…As for colorectal carcinoma, LV-5FU therapy is commonly used in Western countries (8)(9)(10)(11)(12). Moreover, several authors have reported that there are no advantages with CDDP-5FU therapy for colorectal carcinoma (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we experienced a valuable case where CDDP-5FU was very effective for paraaortic lymph node metastases of rectal cancer in a female. Although there are many reports on the efficacy of LV-5FU therapy for colorectal cancer in Western countries (8)(9)(10)(11)(12), we think that CDDP-5FU (UFT) therapy may be useful for the treatment of colorectal cancer by an appropriate protocol and the prevention of side effects such as vomiting and renal disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, once a tumour has spread beyond the colonic wall, the prognosis is much poorer [1,2]. The most studied therapy for advanced CRC is the combined cytotoxic agents 5‐fluorouracil and levamisole which achieves only a 20–40% objective remission rate with only a marginal improvement in survival [3,4]. One strategy subject to much investigation has been the use of monoclonal antibodies (mabs) directed against CRC‐associated antigens [5].…”
Section: Introductionmentioning
confidence: 99%